Image processing and deep learning approach to evaluate earthquake resistance of urban buildings - Ahmed, Yasin; Alam, Tawsiful; Shakil, Md. Hasibur Rahman; Hossain, Md. Tanjidul (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.